Integrasi Doutoku (Pendidikan Moral) dan Life Skill pada Kurikulum Pendidikan Jepang serta Perbandingannya dengan Indonesia: Penelitian - Sesaria Prima Yudhaningtyas; Hartini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Strengthening moral education and life skills is an urgent need amidst globalization and advances in digital technology. Education is no longer solely cognitively oriented; it must balance character development, ethics, and life skills. Japan is known for consistently integrating moral education and life skills into its national curriculum through a holistic approach. This study aims to analyze the integration of moral education and life skills in the Japanese education curriculum and compare it with the education curriculum in Indonesia. The research method used is library research by reviewing various scientific sources in the form of journals, books, and relevant education policy documents. The results of the study indicate that the Japanese curriculum is based on a holistic education philosophy (zenshin kyōiku) which emphasizes the balance of cognitive, affective, and psychomotor aspects through the Chi–Toku–Tai principle. Moral education (dōtoku) and life skills are implemented in an integrated manner through learning activities, school culture, and students' daily activities. Compared to Indonesia, the Japanese curriculum is more consistent in building character, discipline, social responsibility, and work ethic from elementary school. These findings encourage the integration of moral education, life skills, positive school culture, and balanced assessment into the national curriculum.